2000
DOI: 10.1074/jbc.m003245200
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ5, a Novel Potassium Channel Broadly Expressed in Brain, Mediates M-type Currents

Abstract: KCNQ2 and KCNQ3, both of which are mutated in a type of human neonatal epilepsy, form heteromeric potassium channels that are expressed in broad regions of the brain. The associated current may be identical to the M-current, an important regulator of neuronal excitability. We now show that the RNA encoding the novel KCNQ5 channel is also expressed in brain and in sympathetic ganglia where it overlaps largely with KCNQ2 and KCNQ3. In addition, it is expressed in skeletal muscle. KCNQ5 yields currents that activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
391
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(410 citation statements)
references
References 41 publications
(64 reference statements)
14
391
3
2
Order By: Relevance
“…Figure 2 shows that heterologous expression of homomeric WT Kv7.5 channels yielded voltage-dependent K þ currents that activated slowly upon depolarization with a V 1/2 of activation of À46.2 5 1.8 mV (n ¼ 7), as has been described previously. 8,21 All four aberrant proteins exhibited robust functional expression when expressed as homomers. Compared with WT channels, each altered channel modified gating properties (Figures 2 and 3), and this was evident in the activation (Figure 2A) and deactivation ( Figure 3A) current traces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows that heterologous expression of homomeric WT Kv7.5 channels yielded voltage-dependent K þ currents that activated slowly upon depolarization with a V 1/2 of activation of À46.2 5 1.8 mV (n ¼ 7), as has been described previously. 8,21 All four aberrant proteins exhibited robust functional expression when expressed as homomers. Compared with WT channels, each altered channel modified gating properties (Figures 2 and 3), and this was evident in the activation (Figure 2A) and deactivation ( Figure 3A) current traces.…”
Section: Resultsmentioning
confidence: 99%
“…Kv7.5 subunits might also co-assemble with Kv7.3 subunits in vivo to contribute to the M-current, 8,21 as well as KCNE1 and KCNE3 (MIM: 604433), which are endogenously expressed in Xenopus oocytes, and we have not explored the effect of the de novo mutations in such protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Linopirdine and its more potent analog XE991 have been useful in the study of heterologously ex- M. Although linopirdine and XE991 also block other voltagedependent currents (5,26,38), they do so at higher concentrations (IC 50 Ͼ100 M). We found that the M-type current in RPE cells was quite sensitive to block by linopirdine, with an apparent IC 50 of 0.5 M. Consistent with our previous finding (41), XE991 was also effective, with an apparent IC 50 of 0.3 M. The IC 50 values for the block of the M-type current by linopirdine and XE991 are similar to those of KCNQ1, with IC 50 for block of 9 and 0.8 M, respectively (35), but are about an order of magnitude lower than those of homomeric KCNQ4 and KCNQ5 channels, with IC 50 of 6 -14 and 16 -75 M, respectively (18,27,30). This would seem to argue against the involvement of KCNQ4 or KCNQ5 channels in the M-type current and in favor of KCNQ1, but it is possible that the M-type channel sensitivity to these blockers is influenced by interactions with KCNE subunits or other factors.…”
Section: Discussionmentioning
confidence: 98%
“…This profile holds true for all the neuronal K v 7 channel subtypes, whereas for the K v 7.1 subtype both enantiomers block the current. In light of the presence of K v 7.2/7.3 (Saganich et al, 2001) and K v 7.5 (Schroeder et al, 2000a) in the amygdala, and the absence of K v 7.1 in the brain, this implies positive modulators of these channels have a potential as anxiolytics.…”
Section: Discussionmentioning
confidence: 99%